2014
DOI: 10.1186/1471-2334-14-269
|View full text |Cite
|
Sign up to set email alerts
|

Lower than expected hepatitis B virus infection prevalence among first generation Koreans in the U.S.: results of HBV screening in the Southern California Inland Empire

Abstract: BackgroundHepatitis B virus (HBV) infection is prevalent in Asian immigrants in the USA. California’s Inland Empire region has a population of approximately four million, including an estimated 19,000 first generation Koreans. Our aim was to screen these adult individuals to establish HBV serological diagnoses, educate, and establish linkage to care.MethodsA community-based program was conducted in Korean churches from 11/2009 to 2/2010. Subjects were asked to complete a HBV background related questionnaire, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 22 publications
(21 reference statements)
1
18
2
Order By: Relevance
“…10,11 Korean Americans, a rapidly growing ethnic community and the fifth largest among Asian American groups in the United States, report the second highest incidence rates of liver cancer and the highest liver cancerrelated mortality rates. 12 The prevalence of hepatitis B surface antigen positivity also is high among US Korean adults, particularly among Korean men, ranging from 4.9% to 7.5% [13][14][15] compared with 0.3% to 0.5% in the general population. 5 However, estimated rates of Korean Americans who have ever been screened for HBV are 32% to 56% and of those who remain susceptible to future infection, only 38% have ever been vaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Korean Americans, a rapidly growing ethnic community and the fifth largest among Asian American groups in the United States, report the second highest incidence rates of liver cancer and the highest liver cancerrelated mortality rates. 12 The prevalence of hepatitis B surface antigen positivity also is high among US Korean adults, particularly among Korean men, ranging from 4.9% to 7.5% [13][14][15] compared with 0.3% to 0.5% in the general population. 5 However, estimated rates of Korean Americans who have ever been screened for HBV are 32% to 56% and of those who remain susceptible to future infection, only 38% have ever been vaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicate higher rates of HBV screening and vaccination among Chinese and Korean Americans in metropolitan New York compared with studies in other locations, where HBV screening rates range from 35.0% to 54.5% 11,15,2325 and vaccination rates range from 24.7% to 45.6%. 11,15,22,24,25 This may be related, in part, to the community-based, city-wide HBV screening programs in NYC that were conducted between 2005 and 2008. 13,46 In addition, our findings showed that socio-demographic variables are not uniformly associated with screening and vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Studies in US locations outside of NYC have also documented high HBV prevalence among Chinese Americans, between 5.5% and 21%, 14–18 and studies among Korean Americans report a prevalence between 0.7% and 17.9%. 15,1822 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 A large screening study in first generation Koreans in Southern California found a lower than expected HBV prevalence (3%), a continued need for vaccination, and a need for screening despite a reported history of vaccination. 12 A study from the Netherlands of selective screening for hepatitis B and C in immigrants from Afghanistan, Iran, Iraq, the former Soviet Republics, and Vietnam found a prevalence of chronic HBV infection of 9.5% in the Vietnamese population. 13 Data from a clinic caring for immigrants in Greece report that 11.1% of immigrants from Africa tested positive for HBsAg, 13% from Asia, and 9.1% from Europe.…”
mentioning
confidence: 99%